Debt overhang, liquidity constraints and adjustment incentives - Bert Hofman; Helmut Reisen (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
Investment in most heavily indebted countries has been weak since 1982. Several papers (Krugman, 1988; Corden, 1988; Sachs, 1989) have subsequently established the debt overhang proposition: the existence of a heavy debt burden reduces the incentive to invest.1 This proposition has given an important rationale for the 1989 shift in international debt management, emphasizing debt relief rather than new money for problem debtors. This paper will raise doubts against the debt overhang proposition: Its analytical implications are found to be ambiguous, its empirical content is found to be weak. We conclude, that investment in the average debtor country is likely to benefit more from new lending than from debt reduction.
Keywords: 330; Auslandsschuldendienst; Gesamtwirtschaftliche Investitionstheorie; Konsumtheorie; Entwicklungsländer